Priests Petitioning the Police (P.Brit.Mus. EA 10650): Temple Taxes, Temple Land, and Withheld Yields - Winkler, Andreas (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
The article contains the edition and discussion of a rarely encountered form of petition ( ꜥn-smy ) from the Ptolemaic Fayum, which today is kept by the British Museum in London. The text was submitted by a lesonis of Soknebtunis to the chief of police in Mouchis. The document concerns a dispute between two priests from two different localities, Kerkeneith and Tebtunis, over agricultural lands and a harvest. The text is not only an addition to the small corpus of such petitions but also informs about juridical, economic, and religious life in the Fayum under the Ptolemies. It furthermore sheds light on business connections among members of various crocodile priesthoods in the Fayum.